The Future of Urban Living: Smart Cities and Sustainable Infrastructure Technologies Proceedings of the 1st International Conference on Advanced Sustainability Engineering and Technology (ICASET’25) - El Mokhi, Chakib; Hachimi, Hanaa; Nayyar, Anand (Sustainable Civil Infrastructures, 2025)
X, 380 p. 133 illus., 116 illus. in color.